Cultivating emotional wellbeing through biophilic design in Malaysian architecture - Ma'rof, Aini Azeqa; Tang, Bernard Wei Kiet; Mohd Noor, Mohd Zairul (Human Resource Management Academic Research Society, 2024)
The integration of biophilic design in Malaysian architecture seeks to reconnect urban dwellers with nature, enhancing well-being and addressing environmental concerns. Despite Malaysia's rich biodiversity and tropical climate, biophilic principles are underutilized, revealing a gap in architectural practice. This research investigates biophilic design's application and effectiveness in Malaysia, emphasizing cultural relevance and stakeholder engagement. By exploring key biophilic elements and their impact on emotional well-being, the study aims to develop strategies tailored to the Malaysian context. Expected outcomes include improved emotional health, productivity, and sustainable urban development, contributing to healthier, more holistic built environments.